Wt1 Positive dB4 Neurons in the Hindbrain Are Crucial for Respiration - Schnerwitzki, Danny; Hayn, Christian; Perner, Birgit; Englert, Christoph (Frontiers in Neuroscience, 2020)
Central pattern generator (CPG) networks coordinate the generation of rhythmic activity such as locomotion and respiration. Their development is driven by various transcription factors, one of which is the Wilms tumor protein (Wt1). It is present in dI6 neurons of the mouse spinal cord, and involved in the coordination of locomotion. Here we report about the presence of Wt1 in neurons of the caudoventral medulla oblongata and their impact on respiration. By employing immunohistofluorescence staining, we were able to characterize these Wt1 positive (+) cells as dB4 neurons. The temporal occurrence of Wt1 suggests a role for this transcription factor in the differentiation of dB4 neurons during embryonic and postnatal development. Conditional knockout of Wt1 in these cells caused an altered population size of V0 neurons already in the developing hindbrain, leading to a decline in the respiration rate in the adults. Thereby, we confirmed and extended the previously proposed similarity between dB4 neurons in the hindbrain and dI6 neurons of the spinal cord, in terms of development and function. Ablation of Wt1+ dB4 neurons resulted in the death of neonates due to the inability to initiate respiration, suggesting a vital role for Wt1+ dB4 neurons in breathing. These results expand the role of Wt1 in the CNS and show that, in addition to its function in differentiation of dI6 neurons, it also contributes to the development of dB4 neurons in the hindbrain that are critically involved in the regulation of respiration.